Probing Electrode Heterogeneity using Fourier-Transformed Alternating Current Voltammetry: Protocol Development. (20th June 2017) - Tan, Sze-yin; Unwin, Patrick R.; Macpherson, Julie V.; Zhang, Jie; Bond, Alan M.
Graphical abstract: Abstract: Fourier-transformed large amplitude alternating current voltammetry (FTACV) provides a sensitive analytical tool for the discrimination of electrode reactions that are complicated by surface heterogeneity. In this paper, it is shown how the FTACV response at a dual-electrode system comprised of different electrode materials having different heterogeneous charge transfer ( k 0 1 and k 0 2 ) can be resolved into its individual electrode kinetics components without prior knowledge of the electrode size ratio ( θ 1 : θ 2 ). This is possible when one process is reversible and the other is quasi-reversible; achievable by careful selection of the FTACV frequency. The applicability of the FTACV method over a wide range of electrode kinetic values and size ratios is considered for conditions under which numerical simulations based on a 1D diffusion model are adequate to describe the mass transport problem.